La Unión General de los Trabajadores en Burgos, 1888-2009 / Carlos de la Sierra - Sierra, Carlos de la
Bibliografía: v. 2, p. 607-616 | Contiene: Primera parte. 1888-1912 (443 p.) -- Segunda parte. 1913-2009 (634 p.)